2013
DOI: 10.1007/s10620-013-2740-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Practice Gaps to Optimize Medical Care for Patients with Nonalcoholic Fatty Liver Disease

Abstract: The majority of providers do not identify NAFLD as a clinically important diagnosis and do not refer to GI/Hep. However, 83 % expressed a need for education on NAFLD. Our data reveal practice gaps within NAFLD care and identify opportunities for targeted education to guide PCPs in the evaluation and management of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 22 publications
3
43
1
1
Order By: Relevance
“…Taken together, this pattern of care reflects low disease awareness among patients and providers, even in the face of multiple metabolic risk factors . These care patterns also reflect perceptions regarding the clinical significance and treatment options for NAFLD held by many providers . This low rate of referral to GI/Hepatology is in line with data from prior studies where 71% of providers reported that they did not refer patients with suspected NAFLD to GI/Hepatology .…”
Section: Discussionsupporting
confidence: 73%
“…Taken together, this pattern of care reflects low disease awareness among patients and providers, even in the face of multiple metabolic risk factors . These care patterns also reflect perceptions regarding the clinical significance and treatment options for NAFLD held by many providers . This low rate of referral to GI/Hepatology is in line with data from prior studies where 71% of providers reported that they did not refer patients with suspected NAFLD to GI/Hepatology .…”
Section: Discussionsupporting
confidence: 73%
“…10 However, NAFLD is one of the most common chronic liver diseases in the United States today that, in a subset of individuals, leads to cirrhosis, and is projected to become the leading indication for liver transplantation by the year 2020. Of the small percentage of patients who had heard of NAFLD (18%), less than half (43%) were informed by their physicians or other medical providers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in patients with NAFLD, an improvement of diagnostic approach alertness is required for underrating the prevalence and the important clinical condition of NAFLD. Clinicians have developed adequate screening [102] . Finally, it is important to underline that ultrasonography (US) is likely inadequate in several subgroups of patients (obese, Child Pugh B or C, alcohol and NASH related cirrhotic) and does not permit the exclusion of the presence of HCC [103] .…”
Section: Hcc In Nafld Cirrhosismentioning
confidence: 99%